ANALISIS POLA KONSUMSI IKAN DI KOTA BENGKULU - Aprianto, Aprianto; Nusril, Nusril; Sriyoto, Sriyoto (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
This study aims to determine the pattern of fish consumption and to analyze factors that affect of it in Bengkulu City. This research was carried out from13 October 2015 until 17 May 2016. The method used to determine the pattern of fish consumption was descriptive method, and the method used to analyze the factors which affect the consumption of fish was multiple linear regression method with Ordinary Least Square (OLS). Based on the results of the study, fish consumption patterns in Bengkulu City was influenced by education and household income, the higher education and household income, the higher the amount of fish consumption and the quality of the fish consumed, the average of household consumption was 15.006 kg / month with the amount of consumption of marine fish is 62.81%, higher than the amount of consumption of freshwater fish (37.19%), and the proportion of expenditure for fish consumption was 16%. Age, family size, household income, price of Nile Tilapia and prices of goods substitution (chicken) affected the rate of consumption of Nile Tilapia significantly, while education variable did not affect the level of consumption of Nile Tilapia significantly. Age, Chub Mackerel prices and the prices of goods substitution (chicken) affected the consumption of Chub Mackerel significantly, while the variables of education, family size, and income did not affect the level of Chub Mackerel consumption in Bengkulu City. Keywords: Consumption, Consumption Patterns, Fish, Household, Bengkulu City